2009
DOI: 10.5194/angeo-27-4069-2009
|View full text |Cite
|
Sign up to set email alerts
|

High latitude magnetospheric topology and magnetospheric substorm

Abstract: Abstract. This study is focused on the problem of the localization of substorm expansion onset. In this context, the high latitude topology of transverse magnetospheric currents has been analyzed. This study has included the radial distribution of plasma pressure near noon, obtained using the THEMIS-B satellite data, the daytime compression of magnetic field lines and the existence of magnetic field minima far from the equatorial plane, given by all geomagnetic field models. As a result, the dayside integral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This type of current lines also appears in the magnetohydrodynamic (MHD) models of high latitude transverse currents (Liemohn et al 2011 ). Initial estimates of CRC intensities have been made by Antonova et al ( 2009a , b ) and Kirpichev and Antonova ( 2014 ). Thus, the existence of the CRC, which is not included in existing geomagnetic field models with fixed geometry, poses a problem for mapping the auroral regions to the equatorial plane, or, more exactly, to the surface of minimal magnetic field values.…”
Section: Resultsmentioning
confidence: 99%
“…This type of current lines also appears in the magnetohydrodynamic (MHD) models of high latitude transverse currents (Liemohn et al 2011 ). Initial estimates of CRC intensities have been made by Antonova et al ( 2009a , b ) and Kirpichev and Antonova ( 2014 ). Thus, the existence of the CRC, which is not included in existing geomagnetic field models with fixed geometry, poses a problem for mapping the auroral regions to the equatorial plane, or, more exactly, to the surface of minimal magnetic field values.…”
Section: Resultsmentioning
confidence: 99%
“…In magnetostatic equilibrium, it is possible to calculate the current density knowing the plasma pressure and magnetic field. Antonova et al () estimated the value of the transverse currents in the inner magnetosphere and showed that the total transverse current at the dayside field lines is comparable with the total transverse current near midnight at the same geocentric distances. This means that this current closes inside the magnetosphere, forming a high‐latitude continuation of the ordinary RC (Antonova et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure presents the schematic view of the cut ring current shown by the yellow ribbon. The initial verification of the existence of such a current was done by analyzing the radial profiles of plasma pressure gradients obtained from the THEMIS‐B satellite data (Antonova et al, ) but an extensive analysis of the global plasma pressure distribution is still required.…”
Section: Main Current Systemsmentioning
confidence: 99%